Detection of virulence factors among Pseudomonas aeruginosa isolated from cats with otitis (Tikrit Journal of Veterinary Science, 2025)
The Pseudomonas aeruginosa is one of the causative agent of otitis in cats. This study aimed to detect the role of some virulence genes of P.aeruginosa strains in the pathogenicity of otitis in cats, especially; oprL, ToxA, ExoS, lasB, and algD. The results showed high repetitions to some of these genes such as lasB which is present in (100%) of isolates, and algD which is present in (63%) of isolates, that reflect its important role in the progressive of disease. This study improve the importance of early detection of the virulence genes to control the veterinary treatment strategies effectively and decrease the chance of developing the antibiotic resistance by the bacteria